Metabolic syndrome and the risk of cardiovascular and all-cause mortality: data of 14-year prospective cohort study in Siberia - G I Simonova; S V Mustafina; O D Rymar; L V Scherbacova; T I Nikitenko; M Bobak; S K Malyutina (Российский кардиологический журнал, 2020)
Aim. To study the risk of cardiovascular and all-cause mortality in patients with metabolic syndrome (MS) according to a 14-year prospective cohort study in Siberia.Material and methods. Based on the data from the Russian arm of the HAPIEE project, we assessed all-cause deaths occurred by 2017 in the population cohort examined at baseline in 2003-2005 (n=9273). The baseline examination included the assessment of blood pressure (BP), anthropometry, levels of fasting triglycerides, high density lipoprotein cholesterol (HDL-C), and blood glucose. The fatal cases in the studied cohort were identified from “Medical death certificates” for the period from February 1, 2003 to December 31, 2017, based on data from the Department of Civil Registration of Death Acts. Cardiovascular death was established using the International Classification of Diseases, the 10th revision (ICD-10): I (0-99).Results. The mortality rate in subjects with MS was 16,6% — 751 deaths (25,1% in men and 11,5% in women), and it was 20-30% higher than in those without MS. Cardiovascular mortality in subjects with MS was 12,6% — 572 deaths (20,5% in men and 8,9% in women), and it was nearly 30% higher than in those without MS. Multivariable Cox regression revealed that among the components of MS, the elevated BP level even with BP ≥135/80 mm Hg had the major impact on increasing the risk of all-cause mortality (HR=1,7 (1,4; 2,1) in men; HR=2,2 (1,7; 2,8) in women) and increasing the risk of cardiovascular mortality (HR=2,2 (1,5; 3,0) in men and HR=2,8 (1,8; 4.3) in women). Among men, already 1 component of MS increased the risk of cardiovascular and all-cause mortality by 2,0 or more times; among women, 2-4 components of MS increased the risk of death by 3 times, and 5 components — by 4.Conclusion. In the studied population sample, cardiovascular and all-cause mortality during the 14-year follow-up in individuals with MS was about 25-30% higher compared to those without MS. The risk of cardiovascular and all-cause deaths in subjects with MS is comparable to the risk in case of blood pressure ≥135/80 mm Hg. With an increase in the number of MS components from 1 to 5, the risk of all-cause and cardiovascular death increases.